Exploring the Allure: What Drives Customers to Embrace Mobile Banking Apps? - Rawat, Dipak Singh (Journal of Nepalese Management and Research, 2023)
This empirical investigation precisely explores the allure that drives customers to embrace mobile banking apps. This paper aims to examine the combined roles that perceived usefulness, perceived ease of use, perceived security and trust, and perceived hedonic motivation play in the adoption of mobile banking apps. It also aims to determine the effect of perceived hedonic motivation as a mediating variable in the relationship between these factors and the allure to embrace mobile banking apps. The research employed a positivist research philosophy and a descriptive research design, utilizing a survey method. Data were collected from 409 users of mobile banking apps from Karnali Province, employing a purposive sampling technique. The study exclusively conducted inferential analysis, employing the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique to achieve its objectives. The study found a statistically significant positive impact of perceived usefulness, perceived ease of use, perceived security and trust, and perceived hedonic motivation on the adoption of mobile banking apps. Additionally, it identified the complementary partial mediating role of hedonic motivation. It accentuated its supportive influence on the relationships between PEoU, PSaT, and PU, and the allure to embrace mobile banking apps. These findings offer actionable insights for practitioners seeking to enhance mobile banking apps’ appeal and user experience, acknowledging the intricate interplay of factors that collectively shape consumer willingness in the dynamic digital finance landscape